2020
DOI: 10.3390/plants9020237
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Anatomical Mechanisms in Wheat to Cope with Salt Stress Induced by Seawater

Abstract: Two pot experiments were conducted in a greenhouse to examine 14C fixation and its distribution in biochemical leaf components, as well as the physiological and anatomical adaptability responses of wheat (Triticum aestivum L.) grown with seawater diluted to 0.2, 3.0, 6.0, and 12.0 dS m−1. The results showed significant reductions in chlorophyll content, 14C fixation (photosynthesis), plant height, main stem diameter, total leaf area per plant, and total dry weight at 3.0, 6.0, and 12.0 dS m−1 seawater salt str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 38 publications
3
35
0
1
Order By: Relevance
“…Water potential of plants at reproductive phases also reduces the cell extension, vascular tissue thickness, flag leaf thickness, mesophyll, and epidermal cell size, which are responsible for the reduction of flag leaf turgidity, flag leaf area, assimilates synthesis, and yield potential (Nassar et al, 2020). Zhang S. et al (2016) reported that relative water content (RWC) declined by 3.5 and 6.7%, compared to their controls in the salt-tolerant, and salt-sensitive cultivars, respectively, after 6 d of 100 mM NaCl exposure.…”
Section: Water Relation To Salinity Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Water potential of plants at reproductive phases also reduces the cell extension, vascular tissue thickness, flag leaf thickness, mesophyll, and epidermal cell size, which are responsible for the reduction of flag leaf turgidity, flag leaf area, assimilates synthesis, and yield potential (Nassar et al, 2020). Zhang S. et al (2016) reported that relative water content (RWC) declined by 3.5 and 6.7%, compared to their controls in the salt-tolerant, and salt-sensitive cultivars, respectively, after 6 d of 100 mM NaCl exposure.…”
Section: Water Relation To Salinity Stressmentioning
confidence: 99%
“…Thus, understanding of morphoanatomical, physiological, biochemical, and molecular mechanisms of wheat responses to salinity stress at each phase of growth is essential to improve breeding techniques and to develop salt-tolerant varieties with genetic modifications. The recent findings indicate that change in leaf and stem anatomical features in different genotypes of wheat are crucial traits to adaptation under salinity stress (Nassar et al, 2020). The research on the physiological changes that occur during leaf senescence due to some stresses has been primarily focused on the loss of photosynthetic pigments, protein degradation, and re-absorption of mineral nutrients (Zheng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Under salt stress, water deficit and wilting occur because of rapid change in the osmotic potential difference between the plant and exterior environment [ 36 , 40 , 44 , 45 ]. Accompanying this water deficit stress are ABA biosynthesis and transportation throughout the plant initiating stomatal closure, among many other responses, and a decrease in photosynthetic pigments and photosynthetic capacity [ 46 ]. In the present study, the height of most cultivars decreased significantly, and leaf length was prone to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the height of most cultivars decreased significantly, and leaf length was prone to decrease. A reduction in the salt-induced growth rate and a related decline in leaf area and plant height occurred [ 46 ]. Additionally, salt stress resulted in a decrease in the development rate of leaf area expansion due to the key role of water during leaf photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nitraria retusa and Atriplex halimus) adapted to extreme salinities above seawater strength, but is not a common trait associated with halophytes (Boughalleb et al, 2009;Parida et al, 2016). The expansion of xylem area without the allocation of resources to expand the root or stem diameter observed as a salt responsive trait in S. parvula is an atypical adaptation among plants to promote growth while being resilient to salt stress (Olson and Rosell, 2013;Nassar et al, 2020). If availability of water can be ensured in agricultural systems even if the water source is brackish, crops that are able to maintain their relative water content within the plant to levels seen in growth optimal conditions (as observed for S. parvula in Fig 5), while allowing uninterrupted transpiration and gas exchange, will serve as better crops resilient to environmental stresses.…”
Section: Xylem Vessel Expansion Across the Root-shoot Continuum Induced By Salt Observed In The Stress Resilient Growth Of S Parvulamentioning
confidence: 99%